1999
DOI: 10.1001/archpedi.153.4.388
|View full text |Cite
|
Sign up to set email alerts
|

Medical Assessment and Legal Outcome in Child Sexual Abuse

Abstract: To examine the relationship of behavioral symptoms, interview disclosures, and physical examination findings with changing legal outcomes in child sexual abuse. Design: Retrospective case series. Setting: Hospital-and community-based multidisciplinary child abuse evaluation teams in the same county in 2 periods. Patients: Children ages 0 to 17 years referred for evaluation of sexual abuse. Main Outcome Measures: Substantiation by child protective services, issuance of a warrant by law enforcement authorities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 21 publications
(34 reference statements)
2
21
1
3
Order By: Relevance
“…Descriptions do exist of the goals and means [8,10,12] and on detection frequencies and strategies [5], but detailed data about the functioning and effectiveness of CPT are available only from the USA [16,24,26,32] and Canada [9,27]. There are some data available from emergency rooms in the UK [3,4], but only one study from a European children's hospital in Switzerland provides a follow-up of patients diagnosed by the CPT 10 years earlier [14].…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions do exist of the goals and means [8,10,12] and on detection frequencies and strategies [5], but detailed data about the functioning and effectiveness of CPT are available only from the USA [16,24,26,32] and Canada [9,27]. There are some data available from emergency rooms in the UK [3,4], but only one study from a European children's hospital in Switzerland provides a follow-up of patients diagnosed by the CPT 10 years earlier [14].…”
Section: Introductionmentioning
confidence: 99%
“…Attaching greater relative forensic weight to the medical component of the jigsaw would assist Group B children. In America, Palusci et al (1999) concluded from a large-scale study of 497 children that:…”
Section: The Impact Of Cleveland On Investigation and Interventionmentioning
confidence: 99%
“…Um instrumento de avaliação englobando comportamento, revelação e achados físicos tem sido usado por muitos médi-cos nos Estados Unidos, mas nunca foi pretendido como triagem para uso na população geral 8 . Após a avaliação médica, a comprovação final do abuso depende da confissão dos autores do crime e de decisões dos sistemas legal e de assistência social da criança, que respondem pela determinação final e dão início aos passos necessários para a proteção da criança 9 .…”
unclassified
“…Crianças abusadas sexualmente vivem em circunstâncias significativamente mais negativas e estressantes do que crianças não abusadas, com famílias mais pobres, pais menos educados, e vivenciam outras situações estressantes além do abuso sexual, o que confunde ainda mais qualquer avaliação 7 . Se, por um lado, sintomas comportamentais e revelações são importantes no tratamento médico e nas investigações dos serviços de proteção, por outro, achados físicos positivos, embora incomuns, são altamente associados com veredictos de culpa 9 . Uma revisão de vários instrumentos de avaliação e triagem existentes para trauma em crianças e adolescentes concluiu que nenhuma medida comporta, sozinha, todas as situações, e que novos instrumentos são necessários para preencher lacunas nos procedimentos de avaliação atualmente disponíveis 6 .…”
unclassified
See 1 more Smart Citation